Інструменти покращення інвестиційного клімату в територіальних громадах: виклики та перспективи для української економіки - Laiko, Oleksandr; Kwiliński, Aleksy (Dr. Viktor Koval, 2017)
Introduction. The actuality of problem of investment activities stimulation and creation of favorable investment climate rises nowadays because of the necessity of additional resources engaging in socio-economic development of Ukraine and due to the administrative reform progress that causes new possibilities for territorial communities investment development. Aim and tasks. The aim of the article is represented by development of theoretical, methodical positions and practically-applied proposals that are to substantiate the instruments of improvement of the investment climate of territories, according to new challenges and opportunities of the decentralization reform in Ukraine. The example of scope of regulatory measures and positions is to be represented and can be implemented to almost any another Ukrainian region or territorial community. Research results. The essence of the category of investment climate is determined in the modern sense and from the point of view of the ensuring of socio-economic development of territorial communities in Ukraine with the special scope on the regional level. As one of the main tools for the improving of the investment climate in the territorial dimension, special (free) economic zones are considered; key advantages and disadvantages of the using of such instrument are identified. The set of measures to the improving of investment climate on the territory of the community is proposed and such means are capable for providing without creating of a separate territorial unit that minimizes geopolitical risks. The measures are aimed on support of economic initiatives of the communities and include instruments of tax support for entrepreneurial activities. A number of non-economic instruments are proposed, which include the mandatory implementation of the strategy for the development of territorial communities, information support of investment activities with the obligatory passportization of advantages and opportunities, concerning the example of the territories of the Ukrainian Black Sea region. Conclusions. Strategic directions of implementation of the conceptual idea of the regulating of the institutional provision of investment climate include law legalization and social introduction of the best practices of investments stimulation. The prospects of future researches in sphere of investment activities regulation are concerned with effective structure of the institutional environment formation.